Kajian Teoritik Terhadap Urgensi Asas Dalam Akad (Kontrak) Syariah - SITI ZAFILAH FIRDAUSIAH FILA (IAIN Langsa, 2020)
The concept of or in sharia transactions is an important element that regulates and determines the relationship between the economic actors (among others) in a transaction that is related to the contract. Sharia sees the validity of the Akad can be said to be fulfilled if it meets the conditions and pillars of contract. Then, there is a basic principle that can stimulate the contract which is the basis of a foundation, basic, point of decline and footing that serves as a corridor in the creation of the contract as well as a corridor to interpret in resolving treaty disputes. Therefore, the principle becomes very important to be further examined in order to understand the various kinds of akad to make the development of contemporary business Akad and become a reference in making contract. This type of research uses library research. There are principles underlying the creation, enforcement and implementation of sharia contracts that include the principle of ibahah, the principle of freedom of law, the principle of consensualism, the principle of promise binding, the principle of balance, the principle of benefit, the principle of trust, the principle of justice, the principle of personnel, and the written principle.